A concept of trophy status in connection with anthropogenic eutrophication of raised bogs in the Khanty-Mansy Pre-Ob region - N. A. Avetov; E. A. Shishkonakova (Бюллетень Почвенного института им. В.В. Докучаева)
A concept of trophy status of bogs in the soil classifications of Russia and Germany and in WRB is reviewed. A list of plant indicators of trophy status in Khanty-Mansy Pre-Ob region is presented. The specific features of anthropogenic eutrophic peat soil are pH > 4.5 (in topsoil) and meso-eutrophic vegetation, forming eutrophic turf over oligotrophic peat. There are several ways of anthropogenic soil formation as a result of oil production impact.